APAKAH SISWA SMP BERPERILAKU JUJUR DALAM SITUASI ULANGAN? - Sri Lestari; Setia Asyanti (Universitas Muhammadiyah Semarang, 2015)
This research aim to describe the forms of honest and dishonest behavior of junior high school student in academic test situation, and to explain what are the reasons of their honest anddishonest behavior. The amount of 187 students, consist of 91 males and 96 females participated tothis research. An open questioan in form of vignete was used to collect data. The result shows that75.59% students choose to be honest in academic test, and 20.86% conduct dishonesty. Thepurposes of honest behavior are to gain a good score, to preserve the honesty, to master acompetency, to feel contented with honesty. While dishonesty was conducted to gain a good scoreand to avoid difficulties. The implications to psychological education is discussed.Keywords: academic honesty, students, exploratory research, vignette